Tanzania Economic Update, June 2020 : Addressing the Impact of COVID-19 - World Bank Group (World Bank, Washington, DC, 2020)
State of the economy: In 2019 growth in Tanzania’s economy was again solid, but this year COVID-19is expected to cut GDP growth at least in half and increase poverty. Growth slowdown in Tanzania’smain trade partners has reduced demand and prices for its agricultural commodities and final manufactured goods, and international travel bans and fear of contracting the virus are expected to inhibit the recovery of tourism, which has been one of the fastest-growing sectors in the economy. Domestic business conditions are expected to deteriorate. The current outlook is highly uncertain,and risks are tilted to the downside especially if global demand remains suppressed or government actions are not strong, well-targeted or sustained. The risks for a more negative growthoutlook than the baseline described above are high. Under a severe local outbreak, Tanzania’s health care system would become heavily strained, and self-imposed social distancing could dampenmuch of the economy. This would likely lead to a delayed economic recovery, and Tanzania would face continued pressures to finance additional health spending to save lives and providesupport to protect livelihoods. Even if the outbreak is contained in Tanzania, a protracted/resurging global health crisis that continues in 2021 could undermine global demand, and thus, the Tanzanian economy. Furthermore, even if the global health crisis is contained and Tanzania’s COVID-19 reported cases also decrease, additional trade and logistics restrictionscould continue disrupting global trade during the recovery. Tanzania’s macroeconomic performance has been strong for the last decade, but the current crisis is an unprecedented shock that requires strong, well-targeted and sustained policy response.